DETERMINANT OF ISLAMIC SOCIAL REPORTING ON COMPANY REGISTERED AS INDONESIA SYARIA STOCK INDEX - Zulfikar Ramadhan (Manajemen Bisnis, 2019)
The purpose of this study is to study several factors that influence the Islamic Social Reporting Company. These factors are company size and profitability. The variables in this study are company size and profitability, while the dependent variable is Islamic Social Reporting. The research method uses explanation research with a quantitative approach. The sample of this study is a company registered as the Indonesian Syariah Stock Index in 2016. The sample was selected by purposive sampling method which obtained 179 samples. Data Assumption Test for bias data bias bias. Test of Multiple Linear Regression Analysis, Determination Coefficient Test, Statistical Test and Statistical Test to test the hypothesis. Based on this research, it can be proven that leverage has a positive and insignificant effect on the Islamic Social Reporting Company in the form of the Indonesian Islamic Stock Index, while the positive and significant profitability of the Islamic Social Reporting Company in the form of the Indonesian Islamic Stock Index. In addition, leverage and profitability together have a positive and significant effect on the Islamic Social Reporting Company in the form of the Indonesian Islamic Stock Index.